Tourism and environmental and social sustainability through ethnomarketing in Isla Grande (Archipelago of Nuestra Señora del Rosario, Colombia) - Villarreal-Gómez, Alejandro; Mouthón-Ramos, Paola; Jurado-Almonte, José Manuel (Revista de Estudios Andaluces, 2021)
Isla Grande (Archipelago of Nuestra Señora del Rosario, Colombia) has several peculiarities that justify its investigation. Its environmental wealth and coral, reefs stand out, which is why it has been considered one of the most important national natural parks in the Colombian Caribbean. To this is added that its inhabitants are Afro-descendants and that the ownership of the territory is collective. This entails a particular autonomous local organization process to establish a territorial management and local development model. Tourism has become an opportunity, but it also constitutes a threat to the natural environment. In this way, it has been wanted to plan and manage this activity on the basis of ecotourism and ethnomarketing. In this research there is a commitment from the University of Cartagena de Indias with the environmental sustainability of this unique territory. It has worked with surveys and interviews with natives, tourists and businessmen. Direct observation and participatory workshops have also been important to understand and diagnose tourist activity. This has allowed, among other investigations, to formulate a marketing plan in which the island’s ecotourism potential, the ancestral knowledge of the natives, among other aspects, is promoted and made known, and to contribute hand in hand with the actors premises with their environmental sustainability.